PENGARUH KELOMPOK MANAJEMEN PUNCAK TERHADAP FINANCIAL DISTRESS : STUDI KASUS PADA PERUSAHAAN PERBANKAN DI INDONESIA - Moh. Baqir Ainun (Universitas Medan Area, 2019)
This study aims to identify the influence between top management related to financial distress. This study uses data of banking who listed on the Indonesia Stock Exchange in 2016. The data analysis technique in this research using multiple regression analysis method with the control variable; Return on Assets (ROA), Operational Costs to Operating Income (BOPO), Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and Cash Ratio (CR). The study discusses to support the stewardship theory that considers the top management group to have a mandate to the shareholders to manage the company and maintain the organization. However, the differences in the structure of the top management group will not affect their motivation to avoid financial stress. The results showed that the top management group had no significant effect on financial distress. This result is also shown the condition and structure of the top management group in the company still has the same goal which is to avoid financial distress.